Design of dipicolinic acid derivatives as New Delhi metallo-β-lactamase-1 inhibitors using a combined computational approach. Issue 11 (23rd July 2020) - Wang, Xiyan; Gao, Yawen; Yu, Yiding; Yang, Yanan; Wang, Guizhen; Sun, Lin; Niu, Xiaodi
Abstract: New Delhi metallo-β-lactamase (NDM-1) is the most recent addition to the class of metallo-β-lactamases (MBLs). This enzyme leads to antibiotic resistance in clinical treatments owing to its exertion of hydrolysis activity in almost all clinically available β-lactam antibiotics. Consequently, inhibitors targeting NDM-1 have attracted considerable research attention. However, progress has been slow regarding the study of the quantitative structure-activity relationship (QSAR) of NDM-1 inhibitors. In this study, a three-dimensional QSAR (3 D-QSAR) for NDM-1 inhibitors was established using Topomer CoMFA. The multiple correlation coefficients of the fitting model, leave-one-out cross validation, and external validation were found to be 0.761, 0.976, and 0.972, respectively. Topomer Search was used to design 16 new molecules that inhibit NDM-1 using R-group search from ZINC databases, 10 of which had comparatively high activities against NDM-1. The results indicate that Topomer CoMFA and Topomer Search can be used to design new NDM-1 inhibitors and guide the design of new NDM-1 drugs with good predictive capability. Furthermore, from molecular modeling and binding free-energy calculation, it was found that the newly designed molecules can bind to the catalytic region of NDM-1. Additionally, the newly designed inhibitors formed strong interactions with Ile35, Met67, Phe70, Trp93, His122, His189, Cys208, and His250 around the Zn 2+ -centered active region of NDM-1. These findings will facilitate the development of more effective NDM-1 inhibitors for use as potential antibacterial agents. Communicated by Ramaswamy H. Sarma